(i) 3x4+2x3-15x2+12x-6=0
Let f(x)=3x4+2x3-15x2+12x-6
d/dx(3x4+2x3-15x2+12x-6)=12x3+6x2-30x+12
∴f′(x)=12x3+6x2-30x+12
Here f(1) = - 4 < 0 and f (2) = 22 > 0
∴ Root lies between 1 and 2
x0=1+22=1.5
x0=1.5
1st iteration :
f(x0)=f(1.5)=3⋅1.54+2⋅1.53-15⋅1.52+12⋅1.5-6=0.1875
f′(x0)=f′(1.5)=12⋅1.53+6⋅1.52-30⋅1.5+12=21
x1=x0-f(x0)f′(x0)
x1=1.5-0.187521
x1=1.4911
2nd iteration :
f(x1)=f(1.4911)=3⋅1.49114+2⋅1.49113-15⋅1.49112+12⋅1.4911-6=0.0027
f′(x1)=f′(1.4911)=12⋅1.49113+6⋅1.49112-30⋅1.4911+12=20.3887
x2=x1-f(x1)f′(x1)
x2=1.4911-0.002720.3887
x2=1.4909
Approximate root of the equation 3x4+2x3-15x2+12x-6=0 using Newton Raphson method is 1.4909.
Now again using Newton Raphson Method to find the second root, now assuming initial condition to be -3 because while putting -3, the equation becomes nearer to zero. So the roots may be nearer to -3.
f(x)=3x4+2x3-15x2+12x-6
x0 = - 3
1st iteration :
f(x0)= f(-3) = 3⋅(-3)4+2⋅(-3)3-15⋅(-3)2+(12-3)-6=12
f′(x0)= f′(-3) =
12⋅(-3)3+6⋅(-3)2-(30-3)+12=-168
x1 = x0 - f(x0)f′(x0)
x1 = -3-12-168
x1 = -2.9286
2nd iteration :
f(x1) = f(-2.9286) = 3⋅(-2.9286)4+2⋅(-2.9286)3-15⋅(-2.9286)2+(12-2.9286)-6=0.6459
f′(x1) = f′(-2.9286) = 12⋅(-2.9286)3+6⋅(-2.9286)2-(30-2.9286)+12=-150.0875
x2 = x1 - f(x1)f′(x1)
x2 = -2.9286-0.6459-150.0875
x2 = -2.9243
3rd iteration :
f(x2) = f(-2.9243) = 3⋅(-2.9243)4+2⋅(-2.9243)3-15⋅(-2.9243)2+(12-2.9243)-6=0.0023
f′(x2) = f′(-2.9243) = 12⋅(-2.9243)3+6⋅(-2.9243)2-(30-2.9243)+12=-149.041
x3 = x2 - f(x2)f′(x2)
x3 = -2.9243-0.0023-149.041
x3 = -2.9243
4th iteration :
f(x3) = f(-2.9243)=3⋅(-2.9243)4+2⋅(-2.9243)3-15⋅(-2.9243)2+(12-2.9243)-6=0
f′(x3) = f′(-2.9243)=12⋅(-2.9243)3+6⋅(-2.9243)2-(30-2.9243)+12=-149.0373
x4 = x3 - f(x3)f′(x3)
x4 = -2.9243-0-149.0373
x4 = -2.9243
Approximate root of the equation 3x4+2x3-15x2+12x-6=0 using Newton Raphson method is -2.9243
So, The two roots of our polynomial equation are found to be - 2.9243 and 1.4909.
The remaining two roots are not complex so it can’t be calculated.
-----------------------------------------------------------------------------------------------------------------------------------------------------------
(ii). 2x4 + 3x3 – 13x2 – 6x + 8 = 0
By Hit and Trial method, Putting x = -1 in the above equation:
2(-1)4 + 3(-1)3 – 13(-1)2 – 6(-1) + 8 = 0
0 = 0
Therefore, x = -1 is a solution of the above polynomial equation.
By hit and trial method, again putting x = 2 in the above equation:
2(2)4 + 3(2)3 – 13(2)2 – 6(2) + 8 = 0
0 = 0
Therefore, x = 2 is also a solution of the above polynomial equation.
Now the two roots of this equations are found to be -1, 2.
On dividing (2x4 + 3x3 – 13x2 – 6x + 8) by (x+1).(x-2), we get:
( 2x4 + 3x3 – 13x2 – 6x + 8)/((x+1)(x-2)) = 2x2 + 5x – 4
Now the equation can be written in the form,
2x4 + 3x3 – 13x2 – 6x + 8 = 0
(x + 1) (x - 2) (2x2 + 5x - 4) = 0
Using Quadratic formula on 2x2 + 5x – 4, we get:
x = "-5\/4\u00b1\u221a(\u3016(5\u3017^2+4*2*4)\/4"
x = "-5\/4+\u221a(57\/4)" and x = "-5\/4-\u221a(57\/4)"
So, the all roots of the equation are found to be
Solution: -1, 2, -5/4+√(57/4) and -5/4-√(57/4)
Comments
Leave a comment